Diagnosis of Eye Retinal Diseases Based on Convolutional Neural Networks Using Optical Coherence Images - Sertkaya, Mehmet Emre; Ergen, Burhan; Togacar, Mesut (Ieee, 2019)
In this study, the diagnosis of some diseases in the retina of the eye by using deep learning architectures is intended to be diagnosed. Optical Coherence Tomography device from Choroidal Neovascularization, Diabetic Macular Edema, Drusen and healthy eye retinal images were examined. LeNet, AlexNet and Vgg16 architectures of deep learning were used. In each architecture, the hyper parameters were changed to diagnose these diseases. Results of the implementation showed that exhibit successful results in Vgg16 and AlexNet architecture. Dropout layer structure in AlexNet has been shown to reduce the loss by minimizing loss.
23rd International Conference on Electronics -- JUN 17-19, 2019 -- Kaunas Univ Technol, Palanga, LITHUANIA
Keywords: Biomedical optical imaging; Convolutional neural networks; Medical diagnosis; Supervised learning